2021
DOI: 10.1017/s0266462321001562
|View full text |Cite
|
Sign up to set email alerts
|

PP424 Piloting A Comprehensive Search For eHealth Definitions In The Grey Literature: Preliminary Results From A Systematic Scoping Review

Abstract: IntroductionThe use of information technology within health systems has emerged over the years and the current pandemic has further catalyzed this development. As a result, various definitions of eHealth have emerged. Our objective was to provide an overview of definitions available on the internet to complement the traditional (“white”) literature search.MethodsWe adapted methodological guidelines from the Cochrane Handbook and management sciences to mirror the search in bibliographic databases. A comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It concluded that the cost-effectiveness of the wearable cardioverter defibrillator was highly dependent on the daily cost of the device in China [81]. Another study that examined the cost-effectiveness of portable devices for stroke diagnosis found no evidence of the cost-effectiveness under consideration for stroke diagnosis [82]. Another question that might arise from our results is the clinical effectiveness as well…”
Section: Digital Devices Physiological and Behavioral Data And Sensorsmentioning
confidence: 72%
See 2 more Smart Citations
“…It concluded that the cost-effectiveness of the wearable cardioverter defibrillator was highly dependent on the daily cost of the device in China [81]. Another study that examined the cost-effectiveness of portable devices for stroke diagnosis found no evidence of the cost-effectiveness under consideration for stroke diagnosis [82]. Another question that might arise from our results is the clinical effectiveness as well…”
Section: Digital Devices Physiological and Behavioral Data And Sensorsmentioning
confidence: 72%
“…It concluded that the cost-effectiveness of the wearable cardioverter defibrillator was highly dependent on the daily cost of the device in China [ 81 ]. Another study that examined the cost-effectiveness of portable devices for stroke diagnosis found no evidence of the cost-effectiveness under consideration for stroke diagnosis [ 82 ]. Another question that might arise from our results is the clinical effectiveness as well as cost-effectiveness of different digital devices; for example, portable devices (tablet computers) and wearables (Jawbone UP24) were used to measure physical activity [ 56 ], or implantable cardiac monitors and portable devices (Holter electrocardiogram) were applied to record cardiac parameters [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation